Biosynthesis, Characterization of Curcumin-Capped Zno-Cuo and Chitosan-Curcumin-Capped Zno-Cuo based Nanomaterial as Antibacterial Agent of Escherichia coli - Fatoni, Ahmad; Umli, Afnita Fatmawati; Sriwijaya, Reza Agung; Hilma, Hilma; Hidayati, Nurlisa (Chimica et Natura Acta, 2025)
The biofabrication of the chitosan-curcumin-capped ZnO-CuO and curcumin-capped ZnO-CuO nanoparticles, as well as their ability to combat Escherichia coli bacteria, were the focus of this study. Fourier-Transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and Scanning Electron Microscopy (SEM) were used to examine the chitosan-curcumin-capped ZnO-CuO and curcumin-capped ZnO-CuO nanoparticles, respectively. Both were evaluated using the agar diffusion method as antibacterials against Escherichia coli. Results of analysis with FTIR, between 500 and 700 cm⁻¹, the functional group of Cu-O or Zn-O was seen at its highest point. The functional group of Cu-O and Zn-O in curcumin-capped ZnO-CuO was detected at wavenumber of 621 cm⁻¹ and 507 cm⁻¹, respectively. In chitosan-curcumin-capped ZnO-CuO, the wave numbers of the Cu-O and Zn-O groups were observed at 619 and 653 cm-1 respectively.  According to XRD analysis results, the chitosan-curcumin-capped ZnO-CuO and curcumin-capped ZnO-CuO nanoparticles' crystalline shapes are demonstrated by their respective crystallite sizes of 12.58 and 1.88 nm. Based on the results of analysis with SEM, curcumin-capped ZnO-CuO and chitosan-curcumin-capped ZnO-CuO nanoparticles have a dense surface structure. The average diameter of inhibition zone (clear zone) produced by chit-cur-ZnO-CuO nanoparticles is 14.61 mm, while the clear zone produced by cur-ZnO-CuO nanoparticles is 9.52 mm. Chit-cur-ZnO-CuO has superior antibacterial qualities to cur-ZnO-CuO nanoparticles.